2010
DOI: 10.1007/s11192-010-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of civil war: scientific cooperation in the republics of the former Yugoslavia and the province of Kosovo

Abstract: In this study we investigate the scientific output of Yugoslavia and its successor republics viz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The study's visualization highlights that a strong link between Serbia and Croatia was replaced by a stronger link between Slovenia and Croatia. Interestingly, ethnic tensions did not have a lasting impact on scientific cooperation among Yugoslav scientists (Jovanović et al 2010). These findings for former Yugoslavia resemble those observed for the Gulf states by de Bruin et al (1991).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The study's visualization highlights that a strong link between Serbia and Croatia was replaced by a stronger link between Slovenia and Croatia. Interestingly, ethnic tensions did not have a lasting impact on scientific cooperation among Yugoslav scientists (Jovanović et al 2010). These findings for former Yugoslavia resemble those observed for the Gulf states by de Bruin et al (1991).…”
Section: Introductionsupporting
confidence: 61%
“…By comparing the state of medical publishing in Bosnia and Herzegovina with neighbouring countries (Croatia, Serbia, Montenegro), authors concluded that Bosnia and Herzegovina is behind Croatia and Serbia by following parameters: Total Documents, Total Cites and H index but in front of Montenegro (Masic et al 2016). An intriguing study by Jovanović et al (2010) explored the varying impacts of the civil war in former Yugoslavia on its republics. Serbia, heavily involved in the war and bombarded by NATO forces in 1999, experienced a significant decline in publication numbers and cooperation with other Yugoslav states.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are several published researches dealing with published results of the Republic of Croatia, which until 1991 belonged to the former Yugoslavia as well as the Republic of Serbia (Bencetić Klaić and Klaić 2004;Borić and Strujić 2006;Bencetić Klaić and Klaić 1997;Klaić 1997). Also, an interesting research about effects of civil war on scientific cooperation in the republics of the former Yugoslavia and the province of Kosovo was published in 2010 (Jovanović et al 2010).…”
Section: Introductionmentioning
confidence: 99%